Skrining Fitokimia dan Uji Aktivitas Antibakteri Ekstrak Etanol Daun Gatal (Laportea decumana) Asal Desa Waisala Terhadap Bakteri Staphylococcus aureus - Risman Tunny; Epi Dusra; Sahril Sillehu; Maritje S.J Malisngorar; Anisa Muges (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2024)
Introduction: Itch Leaves (Laportea decumana) is a medicinal plant that grows widely in eastern Indonesia, especially Maluku. This plant usually grows in humid areas, surrounded by or adjacent to sago trees, and near rivers. Local people usually use the leaves to treat various complaints such as pain, fatigue and joint and muscle pain, or as a muscle relaxant. Objective: of this research is to determine the secondary metabolite content of the ethanol extract of itchy leaves (Laportea decumana) and test the antibacterial activity of the ethanol extract of itchy leaves (Laportea decumana) against the growth of Staphylococcus aureus bacteria. Method: Used in this research was the Agar diffusion method with itchy leaf test material using concentrations of 60%, 65%, 70% and 75%, chloramphenicol as a positive control and distilled water as a negative control. Results: research shows that itchy leaf extract (Laportea decumana) at a concentration of 60% has an inhibition zone diameter of 15.5 mm, at a concentration of 65% the diameter of the inhibition zone is 20.5 mm, at a concentration of 70% it has 25 mm, while at a concentration of 75% it has The highest area of inhibition against Staphylococcus aureus is 29 mm. Itchy leaf extract (Laportea decumana) at a concentration of 75% has a strong inhibitory level against Staphylococcus aureus bacteria, namely with an inhibitory zone diameter of 29 mm. Conclusion: There are secondary metabolite compounds in the ethanol extract of itchy leaves (Laportea decumana) and antibacterial activity against the growth of Staphylococcus aureus bacteria.